Süd-Atlantischer Ozean / herausgegeben vom Reichs-Marine-Amt, 1911 - Germany. Reichs-Marine-Amt (Berlin : Reichs-Marine-Amt, 1928)
Kleine Berichtigungen: . 1928 Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; "Nr. 384 (Tit. VIII Nr. 1) Klasse 8."; Includes abbreviation table.; Heavily annotated in pencil, colored pencil and pen Grayscale; 1:12,000,000